Endovascular Therapy for Concurrent Cardio-Cerebral Infarction in a Patient With Trousseau Syndrome - Sakuta, Kenichi; Mukai, Taiji; Fujii, Asako; Makita, Kentaro; Yaguchi, Hiroshi (Frontiers in Neurology, 2019)
Only a few patients have been reported to undergo endovascular therapy for Trousseau syndrome. This is the first report of a patient with Trousseau syndrome who developed synchronous cardiocerebral infarction and underwent endovascular therapy for both. A 55-year-old woman with Trousseau syndrome arising from stage IV ovarian cancer presented with consciousness disturbance, aphasia, and right hemiparesis. Magnetic resonance imaging showed acute cerebral infarction limited to the left basal ganglia and occlusion of the left middle cerebral artery (MCA). Electrocardiography showed ST elevation in leads II, III, and aVF with reciprocal change. Mild elevation of myocardial enzymes was observed in laboratory data. She was diagnosed with synchronous cardiocerebral infarction. Both infarctions were considered as appropriately indicated for endovascular therapy. Since her vital signs were stable, a decision was made to treat the cerebral infarction first. Thrombectomy with a stent retriever was performed, which achieved complete recanalization of the left MCA. Percutaneous coronary intervention successfully recanalized the occluded right coronary artery. She suffered no recurrence of stroke or acute coronary syndrome upon heparin administration. Cardiocerebral infarction caused by Trousseau syndrome is rare and demands optimal planning of endovascular therapy.